Baseline MRI and CSF measurements in cognitively normal individuals as prognostic markers of progression to mild cognitive impairment. (December 2021) - Prosser, Lloyd; Macdougall, Amy; Fiford, Cassidy M.; Sudre, Carole H.; Manning, Emily N.; Malone, Ian B.; Walsh, Phoebe; Goodkin, Olivia; Pemberton, Hugh; Barkhof, Frederik; Biessels, Geert Jan; Cash, David M.; et al.
Abstract: Background: Alzheimer's disease is currently one of our greatest socioeconomic challenges. Understanding the ability of biomarkers to predict clinical progression, prior to significant cognitive decline, is critical when considering secondary prevention strategies. Here we consider the association between a range of single time‐point baseline biomarkers in a cognitively‐normal group and the subsequent risk of developing Mild Cognitive Impairment (MCI). Method: Data from Alzheimer's Disease Neuroimaging Initiative (ADNIGO/2/3) were used. Baseline markers (CSF amyloid 1‐42, CSF ptau, white matter hyperintensities [WMH], microbleeds, whole‐brain volume, and hippocampal volume) were obtained for 192 cognitively‐normal (CN) individuals (controls and with significant memory concern; see table). Longitudinal diagnostic data to calculate conversion time was also collected. Cox regression models were fitted for time to diagnosis of MCI. Models were fitted for each marker separately, and in a fully‐adjusted model (containing all markers); adjustments for total intracranial volume (TIV) were performed when needed. Models were refitted adjusting for baseline age. Result: There was strong evidence that increased WMH volume and lower hippocampal volume were associated with conversion to MCI. This was found in both individual models, and in the fully‐adjusted model (see figure). Decreased whole brain volume, CSF amyloid, and increased microbleeds were found to be associated with conversion to MCI when considered individually but not in a fully‐adjusted model. CSF ptau was not associated with conversion, either individually or in the fully‐adjusted model. Adjustments for baseline age did not materially change results. Conclusion: Single time‐point baseline measurements of increased WMH and decreased hippocampal volume were independently predictive of subsequent progression to MCI. Hippocampal volume and WMH may represent different processes; lower hippocampal volumes representing greater neurodegeneration and WMH as a surrogate marker of numerous pathologies, including cerebrovascular disease. While decreased whole brain volume, decreased CSF amyloid, and increased microbleeds were predictive of conversion to MCI when assessed separately, their non‐significant association in the fully‐adjusted model suggests that these are not as strongly predictive of conversion.